Isolated and Combined Laser Acupuncture and Occlusal Device Therapy in TMD Myalgia: A Randomised Controlled Clinical Trial - Brant, Camila Freire; da Costa Siqueira, Letícia; Malaquias, Lara Kramer Chiomark; de Assis, Ariadne Juliany Goulart; Soares, Lélio Fernando Ferreira [UNESP]; Contente, Marta Maria Martins Giamatei; Pigossi, Suzane Cristina; de Faria Almeida, Daniel Augusto (Wiley, 2025)
BACKGROUND: This study aimed to assess the effectiveness of the occlusal device (OD), laser acupuncture therapy and their combination in treating temporomandibular dysfunction (TMD). METHODS: A total of 104 participants (84 women and 20 men), diagnosed with TMD of Muscular Origin, were randomised into three groups: OD group (n = 34): OD; LAT group (n = 34): laser acupuncture (LAT) and ODLAT group (n = 36): OD and LAT. Pain intensity, mandibular mobility and oral health-related quality of life (OHIP-14) were assessed before treatment and at 0, 2, 4 and 12 weeks. RESULTS: The three treatment modalities reduced self-reported pain (OD-p < 0.0001; LAT-p = 0.0005; ODLAT-p < 0.0001) and increased voluntary mouth opening over 12 weeks (OD-p = 0.0005; LAT-p < 0.0001; ODLAT-p < 0.0001). The ODLAT group experienced less pain than the OD group at weeks 2 (p < 0.0001) and 4 (p = 0.047) and showed greater mouth opening at weeks 2 (p = 0.002), 4 (p = 0.001), and 12 (p = 0.008). The LAT and ODLAT groups had significant improvements in pain reduction post-treatment at weeks 0 and 2 (p < 0.0001). The ODLAT group exhibited superior mouth opening after sessions at week 2 (p = 0.002), 4 (p = 0.001) and 12 (p = 0.008) in comparison with other groups. While all therapies reduced OHIP-14 scores, the ODLAT group exhibited significantly lower scores at re-evaluation (p = 0.003). CONCLUSIONS: ODLAT therapy resulted in superior improvements in the myofascial pain symptoms in comparison to the individual treatments.